(untitled) (Orthodontic Journal of Nepal, 2018)
Introduction: Orthodontic treatment is a highly technique sensitive process; which takes long duration and its success depend on many factors. Patient cooperation is one of the important determinants of orthodontic treatment. Objective: To investigate the relationship between patients’ cooperation and orthodontic treatment result as rated by the orthodontist. Materials & Method: Orthodontic Patient Cooperation Scale (OPCS) was used to evaluate 57 orthodontic patients’ cooperation who had undergone active orthodontic treatment in Nobel Medical College Hospital, Biratnagar from 2014 January to 2017 June and were under retention phase. Orthodontic treatment results of these patients were graded as good, acceptable and poor by the orthodontist. Independent t-test was applied to test the mean of OPCS score, the treatment result and gender. Result: Mean OPCS score was higher in good treatment result category; as the OPCS score increased treatment result improved, which was statistically significant (p < 0.01). Conclusion: Orthodontic patients’ cooperation is a strong determining factor for positive treatment outcome.